2020
DOI: 10.1111/apa.15270
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of COVID‐19 in children shows milder cases and a better prognosis than adults

Abstract: Aim:The coronavirus disease 2019 pandemic has affected hundreds of thousands of people. Data on symptoms and prognosis in children are rare. Methods:A systematic literature review was carried out to identify papers on COVID-19, which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), using the MEDLINE and Embase databases between January 1 and March 18, 2020. Results:The search identified 45 relevant scientific papers and letters. The review showed that children have so far account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

110
2,017
11
248

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,120 publications
(2,386 citation statements)
references
References 60 publications
110
2,017
11
248
Order By: Relevance
“…At present, most of the paediatric data are from Chinese studies; of these, many also included children without a laboratory diagnosis and in them, the disease seems to have taken a more severe course than in children with laboratory-confirmed disease [8]. According to some authors, this may be because a number of children improperly categorised as having COVID-19 might have been infected by other aggressive pathogens [11].…”
Section: Discussionmentioning
confidence: 99%
“…At present, most of the paediatric data are from Chinese studies; of these, many also included children without a laboratory diagnosis and in them, the disease seems to have taken a more severe course than in children with laboratory-confirmed disease [8]. According to some authors, this may be because a number of children improperly categorised as having COVID-19 might have been infected by other aggressive pathogens [11].…”
Section: Discussionmentioning
confidence: 99%
“…They found an elevated vulnerability to SARS-CoV-2 among infants, with a proportion of severe and critical cases of 10.6% in this age group (40 out 379 infants). However, the majority of severe and critical cases in the study were not SARS-CoV-2 confirmed, opening the debate whether other untested pathogens could have been responsible for such clinical observations [11]. In fact, SUN et al [12] showed that among eight children (age range 2 months to 15 years), who were admitted to the intensive care unit, only two (25%) were under the age of 12 months.…”
Section: Introductionmentioning
confidence: 79%
“…The most prominent examples of this in history is smallpox, which had a minor effect on children but was catastrophic in adults [33,34]. Children recover quickly and in general, completely while it severe complications to include death result in adults [35]. Adults may be more susceptible to the virus because they are more likely to be infected with other diseases such as diabetes, high blood pressure or heart disease, which weakens their ability to ward off infection.…”
Section: No Scientific Studies Have Been Done On the 2019-ncov And Brmentioning
confidence: 99%